Paradigma Pendidikan Anak dalam Keluarga di Era Digital (Perspektif Pendidikan Islam) - Tian Wahyudi (Ri'ayah: Jurnal Sosial dan Keagamaan, 2019)
This article discusses the paradigm of child education in the family in the Digital Age in the perspective of Islamic education. Digital technology as the main feature of the digital era has two different sides, one side provides benefits, on the other hand causes damage. The benefits include ease of various aspects of the information needed, the presence of a variety of educational media and other positive content. Whereas the damage includes the strengthening of instant culture, the ease of children to access various inappropriate content, the rise of various criminalization in cyberspace etc. The paradigm of family education built in the digital era should pay attention to the reality of the present condition. This refers to the reality of the current generation that is very close to the digital world. Therefore, the educational approach should also be adapted to the conditions of children in this era. The important efforts that parents can make towards their children's education in the family are: (1) able to understand the potential and development of children; (2) able to understand the educational content that must be transmitted to their children; (3) able to recognize digital media both aspects of benefits and negative impacts; (4) able to use digital media as a means of education.